Operational Resilience of Smallholder Palm Oil Supply Chains in West Africa: A Multi-Country Comparative Study - Tolo, Mikel (Yayasan Gema Bina Nusantara, 2025)
This research investigates the operational resilience of smallholder palm oil supply chains across key West African producers, specifically Nigeria and Ghana. In the face of increasing market volatility and climate-related disruptions, understanding how small-scale farmers maintain supply continuity is essential for regional food security and economic stability. Utilizing a multi-country comparative framework, this study analyzes the integration of logistics, financial access, and collaborative networks as drivers of resilience. The findings indicate that while smallholders possess inherent adaptive strategies, institutional voids and fragmented digital infrastructure significantly hinder their scaling capabilities. By evaluating these operational dynamics, the research provides strategic recommendations for policy-makers and agribusiness leaders to strengthen the palm oil value chain through targeted technological interventions and inclusive managerial practices.